Serological evidence of West Nile virus circulation in Indonesia: Initial insights into an underrecognized flavivirus threat - Yora Permata Dewi; Rintis Noviyanti; Leily Trianty; Enny Kenangalem; Frilasita Aisyah Yudhaputri; Matthew J. Grigg; Jeremy P. Ledermann; Ann M. Powers; Eric C. Mossel; Khin Saw Aye Myint (PLoS ONE, 2026)
West Nile virus (WNV) is a mosquito-borne flavivirus primarily transmitted by Culex species and maintained in a bird–mosquito–bird cycle. Though WNV is not considered endemic to Indonesia, sporadic molecular and serological findings suggest possible under-recognized circulation. To examine this possibility, we conducted a cross-sectional serosurvey of 569 archived serum and plasma samples collected between 2021 and 2023 from non-febrile individuals, including blood donors in Papua and community-based participants in Kalimantan. Samples were initially screened using a commercial WNV IgM Enzyme Linked Immunosorbent Assay (ELISA), IgM-positive and equivocal samples were further tested with IgM ELISAs against closely related flaviviruses, including dengue virus (DENV), Japanese encephalitis virus (JEV), and Zika virus (ZIKV). WNV-reactive IgM was initially detected in 9 (1.58%) samples, with 7 (1.23%) additional equivocal results. After additional testing, the WNV IgM seroprevalence was 0.35%, while 1.76% showed cross-reactivity to other flaviviruses. These cases spanned regions including North Kalimantan and Papua, where evidence of WNV-related exposure was previously reported. Detection of WNV-reactive IgM in asymptomatic individuals suggests potential silent or undetected circulation of WNV in Indonesia. Given diagnostic cross-reactivity and IgM persistence, further studies using molecular tools, plaque reduction neutralization test (PRNT), IgG testing, and entomological data are needed to clarify WNV epidemiology and inform surveillance strategies in the region.